Prudent spending helps buffer rising costs - New Sabah Times English, (KK) (New Sabah Times English (KK), 2014)
KUALA LUMPUR: The careful planning of daily expenditure is still the best way to face the rising living cost, a topic of much debate of late. Many feel that advance planning has helped them deal with the rise in prices of goods and services including sugar, fuel and electricity tariff following the subsidy rationalisation by the government.